Pengaruh Jumlah Pendaftar terhadap Jumlah Mahasiswa Baru di Fakultas Agama Islam Universitas Ibn Khaldun Bogor - Hakiem, Hilman; Wicaksono, Matius Rangga (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
One of the essential stages in the world of education is Higher Education. UIKA Bogor is one of the private universities in Bogor City. FAI is the largest faculty in terms of the number of students at UIKA Bogor. The number of applicants is an important element in determining the size of the number of new students admitted. The purpose of this research is to find out how real the effect of the number of applicants is on the number of new students at FAI-UIKA Bogor based on data 2014/2015 to 2020/2021. The method used is simple linear regression. By using the Minitab 19 software, the results showed that the number of applicants had a significant effect on the number of new students. Every increase of 1 registrant will increase the number of new students by 0.4476. The variable number of registrants can explain 83.27% of the data diversity. Keywords: FAI-UIKA Bogor, number of applicants, number of new students